Why did i become a social media follower? an integrative literature review - Cai, Jinchi; Osman, Syuhaily; Haron, Sharifah Azizah (2024)
Background: Social media drives marketing, with users turning into influencers, leading to influencer marketing. As human influencers (HIs) and virtual influencers (VIs) exist, understanding why individuals follow HIs or VIs is crucial. Methods: Literature on followers’ motivations were found in Scopus and CNKI databases, and the sample was collected manually. Data extraction and summarization followed search, screen, select, critical appraisal, and thematic analysis, using the Modified PRISMA 2020 flow diagram and MMAT tool as guides. Findings: Twenty-one articles were reviewed, revealing seven motivations for following both HIs and VIs. The followers of HIs are primarily driven by meeting their own needs, while those following VIs are often motivated by curiosity about the identity of the VIs, their operators, and underlying technology. Conclusion: Current research explores followership motivation for HIs, with a limited focus on VIs. As the field of VIs is still relatively under-researched, future research could further expand the exploration of the impact of VIs and their relationship with followers.